Issues of Family-Community Cooperation in Educating Moral Qualities in Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the interaction of family and community institutions in the process of forming moral qualities in students, their role in the educational process, and effective cooperation mechanisms. The study examines the impact of the family and community environment on child upbringing, national traditions and modern pedagogical approaches to moral education. It also analyzes the effectiveness of practical forms of cooperation - meetings with parents, educational events with the participation of community activists, and spiritual and educational conversations with young people. At the end of the article, proposals and recommendations are made for further improving family-community cooperation.